Pengorganisasian dalam Lembaga Pendidikan Tinggi - Suardi Suardi; M. Amri Nasution; Messiono Messiono (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Higher education is the level of education after secondary education which includes diploma, undergraduate, masters, specialist and doctoral education programs organized by universities. In the government regulation of the Republic of Indonesia Number 30 of 1990 concerning tertiary institutions that higher education is education at a higher level than secondary education in the school education pathway. Higher education is an education that becomes the final terminal for someone who has the opportunity to study at the highest level through school education. Education has an important role in producing reliable human resources. Education service providers have an obligation to create quality human beings through an effective educational process. In general, education service providers in Indonesia consist of two types of services, namely education provided by the government and the community. Higher education can be organized by educational units organized by the Government, in this case other departments or departments or other Government agencies, or by educational units organized by the community. Academic implementers in the field of education can take the form of faculties, departments, or laboratories. The faculty coordinates and/or implements academic and/or professional education in one or a set of certain branches of science, technology and/or arts. The department carries out academic and/or professional education in one or a set of certain branches of science, technology and/or art. The department carries out academic and/or professional education in one or a set of certain branches of science, technology and/or art. Laboratories/studios support the implementation of education in majors in academic and/or professional education.